If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = -2 + y Solving 9 = -2 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 9 + -1y = -2 + y + -1y Combine like terms: y + -1y = 0 9 + -1y = -2 + 0 9 + -1y = -2 Add '-9' to each side of the equation. 9 + -9 + -1y = -2 + -9 Combine like terms: 9 + -9 = 0 0 + -1y = -2 + -9 -1y = -2 + -9 Combine like terms: -2 + -9 = -11 -1y = -11 Divide each side by '-1'. y = 11 Simplifying y = 11
| (6p+5)=18+15 | | 4(m-5)=2(m+3)+4 | | 3n+5-2n=-2 | | -8n=-40 | | 3t^2-16t+26=0 | | 6/5(5k+2)=-36 | | 2x+40(5x)=360 | | 2(x+8)=14x | | -6(1+4n)=-6n+6(n-9) | | h(-4)=7-2(-4) | | 4x+17=180 | | d/3.2=48 | | 2x-20i=8-4yi | | 5(2q+4)=2(4q-6) | | -6x+30=3(x-5) | | g(-4)=5(-4) | | 345=562.5-7.5x | | 4x(7)=70 | | 6/5(5k+2)=36 | | 4x-17+(3x+11)=180 | | 3+x/2=7 | | Y=-0.1x^2+6x+120 | | 4b+16+3b=46 | | pr=qs | | -21x^2+44x-15= | | 3x+5y-2z=22 | | 2(3m-4)=5(m+7) | | 12=10c | | 4b+16+2b=4b | | 6(0)+3X^2=2 | | 2(5+4n)=10(1-9n)+7n | | f(-4)=-(-4)+4 |